Adolescent health in the Eastern Mediterranean Region: findings from the global burden of disease 2015 study - Azzopardi, Peter; Jonas, Jost B.; Mokdad, Ali (International journal of public health, 2018)
OBJECTIVES: The 22 countries of the East Mediterranean Region (EMR) have large populations of adolescents aged 10-24 years. These adolescents are central to assuring the health, development, and peace of this region. We described their health needs. - METHODS: Using data from the Global Burden of Disease Study 2015 (GBD 2015), we report the leading causes of mortality and morbidity for adolescents in the EMR from 1990 to 2015. We also report the prevalence of key health risk behaviors and determinants. - RESULTS: Communicable diseases and the health consequences of natural disasters reduced substantially between 1990 and 2015. However, these gains have largely been offset by the health impacts of war and the emergence of non-communicable diseases (including mental health disorders), unintentional injury, and self-harm. Tobacco smoking and high body mass were common health risks amongst adolescents. Additionally, many EMR countries had high rates of adolescent pregnancy and unmet need for contraception. - CONCLUSIONS: Even with the return of peace and security, adolescents will have a persisting poor health profile that will pose a barrier to socioeconomic growth and development of the EMR.
Published online: 3 August 2017
Gesehen am 13.05.2020
GBD 2015 Eastern Mediterranean Region Adolescent Health Collaborators: P. Azzopardi, J.B. Jonas, A.H. Mokdad [und 174 weitere]